2014
DOI: 10.1177/1090198114531783
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Associated Changes in Body Composition, Health Behaviors, and Mood as Predictors of Change in Body Satisfaction in Obese Women

Abstract: A lack of satisfaction with one's body is common among women with obesity, often prompting unhealthy "dieting." Beyond typically slow improvements in weight and body composition, behavioral factors might also affect change in body satisfaction. Age and race/ethnicity (African American vs. White) might moderate such change. Obese women (N = 246; M(age) = 43 years; M BMI = 39 kg/m(2)) initiating a 6-month cognitive-behaviorally based physical activity and nutrition treatment were assessed on possible predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Despite the high levels of overweight and obesity in our study sample, participants reported moderate levels of body satisfaction, which is consistent with previous studies that found positive body image perceptions among obese black women (6,7,9,). Yet, body satisfaction was not related to motivation or confidence in ability to lose weight.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the high levels of overweight and obesity in our study sample, participants reported moderate levels of body satisfaction, which is consistent with previous studies that found positive body image perceptions among obese black women (6,7,9,). Yet, body satisfaction was not related to motivation or confidence in ability to lose weight.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies report that black women are less concerned about weight than women in other racial/ethnic groups (4), that they prefer large body shapes (5), that they have high levels of body satisfaction and self-esteem while overweight or obese, and that they tend not to believe that losing weight will improve quality of life (4,69). Furthermore, studies showed that black women who lost weight were concerned that they appeared too thin or unwell (10) and worried that a petite body frame might be viewed negatively (eg, as scrawny) (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, the significant improvements in all measures ended at month 6, and from months 6–24 the consumption of sweets significantly increased by approximately 20% across groups. Findings were consistent with previous research on weight management interventions that applied cognitive‐behaviorally based self‐management skills in nutrition and physical activity to help facilitate short‐term increases in participants’ FV consumption (Annesi, ; Annesi, Tennant & Mareno, ). Increased FV intake and decreased consumption of sweets were independently associated with short term (6 months) and long term (48 months) weight loss among overweight and obese women in another study (Gibbs, Kinzel, Gabriel, Chang & Kuller, ).…”
Section: Discussionmentioning
confidence: 99%
“…The SCT has shown to be effective in addressing disease prevention and management of conditions like obesity. 20 , 21…”
Section: Methodsmentioning
confidence: 99%
“…The SCT has shown to be effective in addressing disease prevention and management of conditions like obesity. 20,21 A case study design was adopted using information gathered from 2 sources (1) semi-structured interviews and (2) focus groups.…”
Section: Methodsmentioning
confidence: 99%